2021
DOI: 10.1021/acs.jmedchem.1c00133
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptidic, Polo-Box Domain-Targeted Inhibitors of PLK1 Block Kinase Activity, Induce Its Degradation and Target-Resistant Cells

Abstract: PLK1, polo-like kinase 1, is a central player regulating mitosis. Inhibition of the subcellular localization and kinase activity of PLK1 through the PBD, polo-box domain, is a viable alternative to ATP-competitive inhibitors, for which the development of resistance and inhibition of related PLK family members are concerns. We describe novel nonpeptidic PBD-binding inhibitors, termed abbapolins, identified through successful application of the REPLACE strategy and demonstrate their potent antiproliferative acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…However, in the presence of 500 nM of BI2536, upon abbapolin addition, the tracer was measurably displaced from the FL PLK1 with an IC 50 value of 4.85 ± 1.31 μM. Of note, this value is 5.5-fold lower compared to 26.8 ± 5.0 μM, our previously published IC 50 value for this same abbapolin binding to the PBD fragment . Collectively, these findings provide new insights into the recognition of different PLK1 conformations while confirming prior observations that the binding of BI6727 to FL PLK1 enhanced the interaction between PLK1 and a very similar peptide (MAGPMQS­[pT]­PLNGAK) in an in vitro AlphaScreen assay …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, in the presence of 500 nM of BI2536, upon abbapolin addition, the tracer was measurably displaced from the FL PLK1 with an IC 50 value of 4.85 ± 1.31 μM. Of note, this value is 5.5-fold lower compared to 26.8 ± 5.0 μM, our previously published IC 50 value for this same abbapolin binding to the PBD fragment . Collectively, these findings provide new insights into the recognition of different PLK1 conformations while confirming prior observations that the binding of BI6727 to FL PLK1 enhanced the interaction between PLK1 and a very similar peptide (MAGPMQS­[pT]­PLNGAK) in an in vitro AlphaScreen assay …”
Section: Resultssupporting
confidence: 85%
“…Error bars in panels (E) and (F) represent the standard deviation of the mean of soluble PLK1 from the three replicates. (G) Structures of BI2536, BI6727 (volasertib), and abbapolin 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…REPLACE was applied to accelerate the conversion of FLIP to be a nonpeptide PBD inhibitor. 4-Alkylbenzamide derivatives 55 and 56 were identified as lead compounds with reasonable PLK1 PBD inhibitory activity (Figure A). , The carboxylic acid moiety of 55 was a bioisostere of the phosphate group and was important for maintaining the inhibitory activity against the PLK1 PBD. The alkyl chain occupied the hydrophobic groove of the PBD.…”
Section: Recent Progress In Plk1i Development For Cancer Therapymentioning
confidence: 99%
“…Also, 1-thioxo-2,4-dihydro-[1,2,4]­triazolo­[4,3- a ]­quinazolin-5­(1 H )-one derivatives have been reported to potently and selectively inhibit Plk1-PBD . Interestingly, it was recently reported that abbapolins, nonpeptidic Plk1 binding inhibitors, induce Plk1 degradation in prostate cancer cells . However, extensive high-throughput screening has failed to identify PBD-targeting compounds that have high potency and specificity …”
Section: Introductionmentioning
confidence: 99%